Bohóskodás a halállal: (Borbély Szilárd: Istenasszony Debrecen) - Szilágyi, Márton (Studia Litteraria, 2016)
The paper focuses on Szilárd Borbély’s dramas, more particularly on Istenasszony Debrecen, which is his only piece with humorous parts, although it is not a comedy. The play is connected with the literary history works of the author. The main characters are Ferenc Kazinczy and Csokonai: two figures of Hungarian literature in the 18th and 19th century, who Borbély thoroughly studied. I examine the drama from the aspect of revealing Borbély’s expertise as a literary historian, and from the ways its poetic characteristics reveal his knowledge about literary history, especially the latest findings of the Kazinczy research. My paper also reviews the role of dramaturgical innovations, and the belated and ambiguous reception of Borbély’s dramas.